Creation of a multidisciplinary and multicenter study group for the use of 3D printing in general thoracic surgery: lessons learned in our first year experience - Zabaleta J (Dove Medical Press, 2019)
Jon Zabaleta,1 Borja Aguinagalde,1 Iker López,1 Stephany M Laguna,1 Mikel Mendoza,2 Ainhoa Galardi,2 Luis Matey,3,4 Andrea Larrañaga,4 Gorka Baqueriza,5 Ander Izeta61Thoracic surgery service, Donostia University Hospital, IIS Biodonostia, San Sebastian, Spain; 2Radiology service, Donostia Universitary Hospital, San Sebastian, Spain; 3Additive Manufacturing, Ceit-IK4, San Sebastian, Spain; 4School of Engineering, Tecnun-University of Navarra, Pamplona, Spain; 5Additive Manufacturing, Tknika-Basque Centre of Research and Applied Innovation in Vocational Education and Training; 6Tissue Engineering Group, IIS Biodonostia, San Sebastian, SpainIntroduction: In recent years, the use of 3D printing in medicine has grown exponentially, but the use of 3D technology has not been equally adopted by the different medical specialties. Published 3D printing activity in general thoracic surgery is scarce and has been mostly limited to case reports. The aim of this report was to reflect on the results and lessons learned from a newly created multidisciplinary and multicenter 3D unit of the Spanish Society of Thoracic Surgery (SECT).Methods: This is a pilot study to determine the feasibility and usefulness of printing 3D models for patients with thoracic malignancy or airway complications, based on real data. We designed a point-of-care 3D printing workflow involving thoracic surgeons, radiologists with experience in intrathoracic pathology, and engineers with experience in additive manufacturing.Results: In the first year of operation we generated 26 three-dimensional models out of 27 cases received (96.3%). In 9 cases a virtual model was sufficient for optimal patient handling, while in 17 cases a 3D model was printed. Per pathology, cases were classified as airway stenosis after lung transplantation (7 cases, 25.9%), tracheal pathology (7 cases, 25.9%), chest tumors (6 cases, 22.2%) carcinoid tumors (4 cases, 14.8%), mediastinal tumors (2 cases, 7.4%) and Pancoast tumors (one case, 3.7%).Conclusion: A multidisciplinary 3D laboratory is feasible in a hospital setting, and working as a multicenter group increases the number of cases and diversity of pathologies thus providing further opportunity to study the benefits of the 3D printing technology in general thoracic surgery.Keywords: 3d printing, thoracic surgery, multidisciplinary group, preoperative study